Influencing Factors In-Hospital School Education: Exploring the Context From the Teacher’s Perspective - Francisca Jiliberto; Nair Zárate Alva (Continuity in Education, 2025)
Hospital teachers face unique challenges and require specific skills to cope with the demands of teaching within a hospital setting effectively. Additionally, the quality of education in hospital schools (HS) may be affected by factors such as resource availability and coordination with other professionals. This initial study examined the factors influencing education in HSs for hospitalised children with physical health conditions. Teachers from the eight HSs in Catalonia (N = 16) responded to an online questionnaire developed based on a scoping literature review that identified factors reported to influence education in HSs. Employing a mixed-method convergent parallel design, quantitative data from closed-ended questions and qualitative data from comments were analysed in parallel. Results showed that hospital teachers face challenges such as adapting to diverse educational stages and subjects, selecting teaching methods tailored to students’ individual needs, and coordinating with various professionals on a case-by-case basis. They often lack sufficient budgets, consistent access to resources, and opportunities for professional training. Participants’ views on the skills required by hospital teachers align closely with literature findings, as does their perception of the emotional impact of working in a HS. Understanding the unique context of HSs is crucial for stakeholders and policymakers to ensure inclusive and equitable quality education for all.